Racism against indigenous people in higher education: a study from the perspective of critical interculturality - Marta Coelho Castro Troquez; Luana Larissa de Carvalho (Educazione Interculturale, 2024)
The Federal University of Grande Dourados (UFGD) develops positive discrimination aimed at indigenous peoples; however, it still reproduces practices called institutional racism. This work presents results of a research whose main objective was to collect narratives of indigenous higher education students at UFGD regarding their experiences with institutional racism. The research is anchored in the Critical Interculturality perspective (Walsh, 2009). Semi-structured interviews with indigenous students were used as a research methodology. The results show that, despite the progress offered by Affirmative Actions, indigenous students still experience racist manifestations in the higher institution. Many strategies of resistance and reaffirmation of indigenous identities are highlighted by students in Higher Education. The research reinforces the need to think about continued training for professionals who work at the institution, in order to combat racism and build inclusive spaces for indigenous students, which expand beyond the Indigenous Intercultural Faculty, which already has a differentiated proposal.